Raman spectroscopy and its application in nanostructures - Zhang, Shu-Lin, 1935- (Wiley, 2012)
"This book will be a useful contribution to an active area of physics research, and will describe the basic knowledge on three-dimensional (traditional) Raman spectroscopy and then discuss the main features of low-dimensional Raman spectroscopy"--Resumé vydavatele
Keywords: Ramanova spektroskopie; nanostruktury; nanomateriály; Raman spectroscopy; nanostructures; nanostructure materials; monografie; monographs